2010
DOI: 10.1016/j.talanta.2010.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the adsorption performance of a multi-sorbent bed (Carbotrap, Carbopack X, Carboxen 569) and a Tenax TA adsorbent tube for the analysis of volatile organic compounds (VOCs)

Abstract: A comparison between two types of adsorbent tubes, the commonly used Tenax TA and a multi-sorbent bed (Carbotrap, Carbopack X, Carboxen 569) tube developed in our laboratory, has been done to evaluate their usefulness in the analysis of VOCs in ambient air. Duplicate indoor and outdoor samples of Tenax TA and multi-sorbent tubes of 10, 20, 40, 60 and 90l were taken in Barcelona city (Spain) on July and October of 2009. Breakthrough values (defined as %VOCs found in the back tube) were determined for all sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 16 publications
0
63
2
1
Order By: Relevance
“…The performance and reliability has been tested commonly for this type of multibed samplers with similar sorbent compositions. For instance, Gallego et al (2010) investigated relative performance between three sorbent bed tube samplers and a single bed tube (Tenax TA). These authors observed significant differences in measured data between the two tubes from the very volatile compounds (56°C < boiling point [bp] < 100°C and 4 kPa < vapor pressure (20°C) < 47 kPa; e.g., acetone, isopropanol, n-hexane) and alcohols and chlorinated compounds (e.g., 1-butanol, carbon disulphide, dichloromethane, chloroform, carbon tetrachloride, trichloroethylene, and tetrachloroethylene).…”
Section: Collection Of Air Samples and Voc Analysismentioning
confidence: 99%
“…The performance and reliability has been tested commonly for this type of multibed samplers with similar sorbent compositions. For instance, Gallego et al (2010) investigated relative performance between three sorbent bed tube samplers and a single bed tube (Tenax TA). These authors observed significant differences in measured data between the two tubes from the very volatile compounds (56°C < boiling point [bp] < 100°C and 4 kPa < vapor pressure (20°C) < 47 kPa; e.g., acetone, isopropanol, n-hexane) and alcohols and chlorinated compounds (e.g., 1-butanol, carbon disulphide, dichloromethane, chloroform, carbon tetrachloride, trichloroethylene, and tetrachloroethylene).…”
Section: Collection Of Air Samples and Voc Analysismentioning
confidence: 99%
“…Adsorption, absorption and condensation are the three most common non-destructive techniques for the removal/recovery of Cl-VOCs from gas streams [21][22][23][24]. Adsorption with activated carbon (AC) has been widely used for the removal of gaseous organic pollutants [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding breakthrough volumes, studies using a combination of Carbotrap, Carbopack X and Carboxen-569 showed breakthrough volumes lower than 5% for a wide range of VOCs, including benzene, toluene, xylene and alpha-pinene; for acetone, breakthrough volumes were found to be dependent on the volume sampled ( [197]; [199]). Experiments using a mixture of Carbograph 2 and Carbograph 5 also showed low breakthrough volumes (<1%) for a number of VOCs, including o-xylene [201].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not always possible to bring the source of volatiles and the analytical device together. To circumvent this problem, volatile storage containers can be used such as Teflon or Tedlar bags ( [191]; [192]; [193]), canisters ( [194]; [195]), and Tenax TA or Carbotrap/Carbograph thermodesorption tubes ( [196]; [197]; [198]; [199]). Thermo desorption tubes trap different groups of volatiles depending on the sorbent placed inside the tubes, either by diffusion or by pumping the gas through the tube.…”
Section: Introductionmentioning
confidence: 99%